2019
DOI: 10.12998/wjcc.v7.i13.1591
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopic and microscopic transsphenoidal approach for resection of nonfunctional pituitary adenomas

Abstract: BACKGROUND Nonfunctional pituitary adenoma is a common type of pituitary adenoma, which can lead to headache, visual field disturbance, and cranial nerve damage due to increased tumor volume. Neuroendoscopic and microscopic transsphenoidal approaches have been widely used in the resection of nonfunctional pituitary adenomas. However, the clinical efficacy in neuroendoscopic and microscopic surgery is still controversial. AIM To explore the clinical efficacy of neuroendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Thus, the aim of this meta-analysis was to definite whether intraoperative LD can prevent CSF leakage during the perioperative period of pituitary adenomas transsphenoidal surgery. The estimated pooled results showed that intraoperative LD was an effective measure [19]. Intraoperative LD can reduce strain on the arachnoid, making it less susceptible to puncture [11,13,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the aim of this meta-analysis was to definite whether intraoperative LD can prevent CSF leakage during the perioperative period of pituitary adenomas transsphenoidal surgery. The estimated pooled results showed that intraoperative LD was an effective measure [19]. Intraoperative LD can reduce strain on the arachnoid, making it less susceptible to puncture [11,13,20].…”
Section: Discussionmentioning
confidence: 99%
“…The force during tumor resection enhanced tension on the arachnoid, which might tear the arachnoid. A tear of arachnoid increased the risk of CSF leakage [ 19 ]. Intraoperative LD can reduce strain on the arachnoid, making it less susceptible to puncture [ 11 , 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…ER required more aggressive resection of the pseudocapsule which was attached directly to the surface of arachnoid. As a result, the extra process to remove the pseudocapsule from the thin layer of arachnoid enhanced tension on the arachnoid, inducing tearing of arachnoid and CSF leakage [ 7 , 18 ]. In contrast, some studies have suggested that the advantages of ER for anatomical orientation, and removal of a security margin could reduce the risk of opening arachnoid layer with subsequent CSF flow [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…During pituitary surgery, descent of the diaphragm sellae (DS) is occasionally encountered. This can block access for remnant tumor or cause cerebrospinal fluid (CSF) leak due to uneventful rupture of the DS 9) . To prevent early descent of the DS, resection of pituitary tumors is generally performed in a sequential manner from the inferior part to the lateral part and finishing with the superior part 15) .…”
Section: Introductionmentioning
confidence: 99%